Social Reflections of New Normal in Thai Contemporary Short Stories - Soontherotoke, Saiwaroon (Journal of International Studies, Prince of Songkla University, 2024)
The research titled “Social Reflections of New Normal in Thai Contemporary Short Stories” aims to 1) examine the state of Thai society during the period of the COVID-19 pandemic depicted in 112 short stories selected in the project "COVID Transforms Us, Narratives Transform the World," written between July and August 2020, and 2) analyze the writers’ perspectives reflecting the changes in new lifestyles through these short stories. The findings revealed that these short stories present reflections of new social lifestyles, including 1) the use of technology and the internet for remote working or working from home, online shopping, transactions, and entertainment, 2) emphasis on social distancing measures with an increased focus on cleanliness, 3) intense follow-up of news and information, and 4) a struggle for daily life balance encompassing professional and personal life, coping with stress, and living with family in a desirable environment. From the selected short stories, the writers introduce several concepts, including: 1) life balance, 2) education in new lifestyles, 3) search for job livelihoods particularly in an aging society 4) economy and business transactions, and 5) recreation and exposure to nature. This research concluded that creative writing serves as an art form that expresses various societal events. Writers skillfully weaved narratives that relate to life, culture, traditions, and norms during the outbreak of the COVID-19 pandemic. Contemporary history in short stories is a crucial component linking imagination, attitude, and emotion. The survey responses regarding writers’ attitudes indicated that being a writer offers advantages over other professions due to enhanced imagination and positive attitudes, which contributes to happier living. Furthermore, most respondents resided in the up-country, so they experienced less impact from the COVID-19 pandemic compared to urban residents. However, they still urged the government to provide support and opportunities for the registration of professional writers.